The impact of domestic and school air quality on respiratory symptoms among primary school students with different socioeconomic backgrounds - Mostafaee, Masoud (Curtin University, 2010)
Respiratory symptoms including wheezing, tight chest, breathing difficulty, are common childhood disorders, and are the most important reasons for (National Health and Medical Research Council 1996; Rumchev, Spickett et al. 2002; Australian Centre for Asthma Monitoring 2005a)absenteeism in school age children that may decrease the quality of life (Lam, Chung et al. 1998; Penny, Murad et al. 2001). Although genetic background and environmental exposure seem to be the key factors for the development of respiratory symptoms, socio-economic status (SES) may also contribute to the development of those illnesses in children (Rona 2000). To investigate the extent to which socio-economic factors may contribute to the increased prevalence of respiratory symptoms and asthma in Australia we studied respiratory symptoms and asthma among primary school students from low and high socioeconomic backgrounds.Objective: A cross sectional study to determine the impact of school and domestic indoor air pollution on respiratory symptoms among primary school students from different socio-economic backgrounds (low and high) was conducted within the Perth metropolitan area. The study was carried out in three stages: 1) Questionnaire survey, 2) Indoor air quality monitoring in schools, 3) Indoor air quality monitoring in houses.Methods: We studied 104 primary school students from low and high socioeconomic areas of Perth metropolitan between 2007 and 2008. The respiratory symptoms and asthma were assessed with a standardized questionnaire. Schools and domestic environmental monitoring took place 4 in winter and summer in order to determine seasonal differences in concentrations of studied air pollutants. For this purpose 11 primary schools with low and high socio-economic backgrounds were selected. Domestic air qualities were monitored in 90 houses from each area of low and high socio-economic status. SES was derived from means of more than 2 indicators including education and income. The areas of low and high socio-economic status were also determined by the Australian Bureau of Statistics. Exposure levels to some primary indoor air contaminants including Volatile Organic Compounds (VOCs) (μg/m3), formaldehyde (HCHO) (μg/m3) and particulate matter with size 2.5 microns in diameter PM2.5 (μg/m3) and PM10 (μg/m3) were measured in domestic and schools environments. Indoor temperature (TºC) and relative humidity (RH) (%) were also monitored. Multivariate analyses were then used to quantify the effect of relevant factors on the prevalence of respiratory symptoms.Results: Socioeconomic status is a comprehensive index that refers to a broad range of factors, such as level of social communities, income, education, parental occupations and living conditions. School children from low socioeconomic groups showed more respiratory symptoms in this study. Those who had higher SES had fewer asthma and respiratory symptoms. We conclude that low socioeconomic status is itself a risk factor for respiratory symptoms and asthma among school children.Conclusion: Asthma continues to impose a heavy burden on the nation’s health care expenditures, Reduces productivity, and seriously affects the quality of life for individuals with asthma and their families. Asthma is a public health problem that does not have a .quick fix. It will require the combined efforts of individuals with asthma and their families, health care providers, health care institutions, schools, workplace, governments, voluntary organizations, industry, and the general public. Asthma and respiratory symptoms were more common in low socioeconomic status groups. There was no significant support for the hygiene hypothesis.